Is grit the key element to improve life attitude?: a study with military students from Argentina - Barni, María Cecilia (2019)
The main goal of the study is to analyze the link between Grit and Life Attitude, and its relation with the permanence and academic performance of students from the National Defense University. This paper is mainly focused on the link between the first two constructs. Grit is defined as the passion and constancy to achieving goals, to resisting with effort and interest towards challenges and difficulties, which are a leader's attribute (Duckworth, Peterson, Matthews y Kelly, 2007). Life Attitude based on the existential belief that life has a purpose, that persons draw meaning from a variety of sources: recreational and creative activities, personal relationships, achievements (Reker & Woo, 2011).A non-probabilistic sample was formed, for convenience, of 162 students; a sociodemographic questionnaire designed adhoc; the Scale of Determination (Grit Scale) (Duckworth et al., 2007), which is in the process of validation (Tortul and Daura, in evaluation) and the Life Attitude Test (LAP-R (VE-AA)) in the Spanish adaptation of Barni (2017) were administered. Statistical analyses were made from the collected data, in order to corroborate if there were differences in the variables. The first results showed differences according to career and sociodemographic variables; the undergraduate students obtained higher scores in the positive dimensions of the LAP-R than in other researches made in the same geographical context.The work evidences data of interest in the training of defense professionals, for the decision making in the educational style necessary for an integral formation as a lifelong process.